Essential oils, phenology and biotic interactions of the invasive plant Crassocephalum crepidioides (Asteraceae) in Costa Rica (UNED Research Journal, 2022)
ABSTRACT. “Essential oils, phenology and biotic interactions of the invasive plant Crassocephalum crepidioides (Asteraceae) in Costa Rica”. Introduction: Crassocephalum crepidioides (Asteraceae) is an herbaceous species with outstanding ethnobotanical uses in Africa and elsewhere, that has extended invasively in several tropical and subtropical regions around the world. Objective: To identify the chemical composition of the essential oils of C. crepidioides, to observe and measure phenological parameters (growth and development), and to record signs of the interaction of plants with other biotic agents throughout the life cycle in the Central Valley of Costa Rica. Methods: The essential oils were obtained via hydrodistillation in a Clevenger-type apparatus. The chemical composition of the oils was done by capillary gas chromatography (GC/FID and GC/MS). The biological field study was a descriptive account of phenological patterns observed during a year in 45 plants from three places, including vegetative and reproductive phases. Results: The essential oils consisted mainly of terpenoids (91,0 to 98,6%). A total of 231 different compounds were identified in the analyzed samples, corresponding to 94,9-99,3% of the total amount of the oils. The major compounds from the leaf oil were myrcene (67,5%) and β-phellandrene (11,6%), while the stem oil mainly contained myrcene (42,2%) and α-copaene (16,5%). The major constituents of flower oil were myrcene (71,8%) and β-phellandrene (17,2%). In the root oil, (E)-β-farnesene (29,5-46,0%), (Z)-β-farnesene (13,0-15,7%) and (E)-caryophyllene (6,0-6,1%) predominated. The mean height of plants was considerably superior in open and sunny places compared to values in partially shaded habitats. In one of the places, 36% of plants died before completing the life cycle for the most part, due to herbivory that was present in more than 80% of all plants and damaged 100% of their shoot organs (stems, leaves, lateral buds, flower buds, and flowers). November and December were the months with maximal flower anthesis and fruit ripening. Conclusions: This species is recognized as annual, but 2/3 of plants completed their life cycle in 4 to 6 months, and due to herbivory and other environmental factors its propagation shows a considerable reduction.